Stemflow Infiltration Hotspots Create Soil Microsites Near Tree Stems in an Unmanaged Mixed Beech Forest - Metzger, Johanna Clara; Filipzik, Janett; Michalzik, Beate; Hildebrandt, Anke (Frontiers in Forests and Global Change, 2021)
In stemflow, rainfall is collected and channeled to a concentrated soil water input. It can constitute up to 30 % of incident precipitation in some ecosystems. However, the size of the zone influenced by stemflow is unclear, and statistically representative measurement of stemflow (on and in between sites) is scarce. Therefore, whether stemflow creates hotspots of infiltration and potential impacts on forest soils remain subject to controversy. In this study, we investigated the areal dimension of infiltrating stemflow fluxes as well as effects on near-stem soils. We measured throughfall, stemflow and soil properties in high-resolution statistical designs on a mixed forest plot in Germany receiving moderate stemflow. From this data, we modeled the spatial distribution of net precipitation infiltration depth on the plot. Furthermore, we examined soil chemical and physical properties around tree stems to test for and assess a stemflow impact. Results show, that stemflow infiltration areas are much smaller than typically assumed and constitute strong infiltration hotspots compared to throughfall. This is also mirrored in soil properties, which are significantly altered near stems. Here, accelerated soil formation and enhanced translocation processes indicate increased soil water fluxes due to high inputs. Additionally, altered soil hydraulic properties enable quicker soil water fluxes near stems. Our findings attest that even comparatively low stemflow fractions (of gross precipitation) can generate strong hotspots of water and matter inputs, which are impactful to subsequent hydrological and biogeochemical processes and properties. Trees shape their direct soil environment, thereby establishing pathways of preferential water flow connecting the canopy and the deeper subsurface.